PERAN KEPALA SEKOLAH DAN GURU DALAM IMPLEMENTASI KEPEMIMPINAN DIGITAL DI SMA MUHAMMADIYAH TOBOALI MENJADI GENERASI UNGGUL INDONESIA 2045 - Desi, Desi Ari; Suyatno, Suyatno; Zuhaery, Muhammad (Jurnal Kepemimpinan dan Pengurusan Sekolah, 2026)
Digital transformation in education is a crucial element in improving the quality of learning and preparing students for global competition. This study aims to examine the roles of principals and teachers in implementing digital leadership, implementing educational digitalization, and assessing students' digital literacy skills amidst technological developments at Muhammadiyah Toboali Senior High School. This study used a qualitative approach with a case study method, with data collection techniques through in-depth interviews, direct observation, and documentation analysis with the principal, teachers, and students. The results show that the principal acts as a transformational leader who strives to direct and motivate all school members to adopt technology in the learning process. Teachers function as active facilitators in developing students' digital literacy through the use of various technology-based learning platforms and media. The implementation of educational digitalization in schools is evident through the development of a technology-integrated curriculum, the implementation of a digital school administration system, and the use of technological devices in teaching and learning activities. Students' digital skills have significantly improved, particularly in critical thinking skills, creativity, and adaptability to technological developments.